Responsiveness of the Manchester-Oxford foot questionnaire (MOXFQ) compared with AOFAS, SF-36 and EQ-5D assessments following foot or ankle surgery - Dawson, J; Boller, I; Doll, H; Lavis, G; Sharp, R; Cooke, P; Jenkinson, C (2012)
The responsiveness of the Manchester-Oxford Foot Questionnaire (MOXFQ) was compared with foot/ankle-specific and generic outcome measures used to assess all surgery of the foot and ankle. We recruited 671 consecutive adult patients awaiting foot or ankle surgery, of whom 427 (63.6%) were female, with a mean age of 52.8 years (18 to 89). They independently completed the MOXFQ, Short-Form 36 (SF-36) and EuroQol (EQ-5D) questionnaires pre-operatively and at a mean of nine months (3.8 to 14.4) post-operatively. Foot/ankle surgeons assessed American Orthopaedic Foot and Ankle Society (AOFAS) scores corresponding to four foot/ankle regions. A transition item measured perceived changes in foot/ankle problems post-surgery. Of 628 eligible patients proceeding to surgery, 491 (78%) completed questionnaires and 262 (42%) received clinical assessments both pre-and post-operatively. The regions receiving surgery were: multiple/whole foot in eight (1.3%), ankle/hindfoot in 292 (46.5%), mid-foot in 21 (3.3%), hallux in 196 (31.2%), and lesser toes in 111 (17.7%). Foot/ankle-specific MOXFQ, AOFAS and EQ-5D domains produced larger effect sizes (> 0.8) than any SF-36 domains, suggesting superior responsiveness. In analyses that anchored change in scores and effect sizes to patients' responses to a transition item about their foot/ankle problems, the MOXFQ performed well. The SF-36 and EQ-5D performed poorly. Similar analyses, conducted within foot-region based sub-groups of patients, found that the responsiveness of the MOXFQ was good compared with the AOFAS. This evidence supports the MOXFQ's suitability for assessing all foot and ankle surgery. ©2012 British Editorial Society of Bone and Joint Surgery.